Placing the Aurignacian from Banat (Southwestern Romania) into the European Early Upper Paleolithic context - Sitlivy, Valery; Anghelinu, Mircea; Chabai, Victor P.; Niţă, Loredana; Uthmeier, Thorsten; Hauck, Thomas; Baltean, Ionuts; Hilgers, Alexandra; Schmidt, Christoph (Modes de contacts et de déplacements au Paléolithique eurasiatique, 2014)
During the 1983 UISPP congress in Liège, F. Mogoșanu presented the results of his earlier investigations on the Paleolithic in the Romanian Banat. The Upper Paleolithic of this area was viewed as a chronologically late manifestation of the Central European Krems-Dufour type Aurignacian. After a long break in research, new investigations in the settlements at Coșava, Româneşti- Dumbrăviţa and Tincova have been undertaken, leading to an improved knowledge of the regional Upper Paleolithic. The present contribution reports the first results of the comparative techno-typological and attribute analysis of the lithic assemblages at Tincova, Coșava and Româneşti-Dumbrăviţa, involving both old and recently excavated collections. Strengthening the conclusions reached by the lithic studies, the first chronometric assessments (TL and OSL) for the recently excavated open-air site of Româneşti-Dumbrăviţa I place the Aurignacian of this site into an early stage of this technocomplex. However, the attempt for incorporating the regional record into the European Early Upper Paleolithic context remains difficult and raises serious issues regarding the acknowledged divisions of the European Aurignacian and, consequently, the expansion of this cultural phenomenon across Europ